Etil Format sebagai Perlakuan Alternatif terhadap Colletotrichum gloeosporioides pada Stroberi - Ade Syahputra; Nurul Dwi Handayani; Indriani Kusumawati Daud Malvini (Jurnal Fitopatologi Indonesia, 2012)
Ethyl formate (EtF) is alternative fumigant to substitute methyl bromide. The objective of the current study was to obtain an effective dose and exposure time of Etf treatment against Colletotrichum gloeosporioides in strawberry. In vitro test was conducted on colonies of C. gloeosporioides grew on PDA in petri dishes. The fungus was fumigated with Etf at various dose (0, 140, 190, 240, and 290 g m-3) and at various exposure time (1, 2, 3, and 4 hours), in 5 L plastic bags. On in vivo test, agar plugs of C. gloeosporioides (diameter 0,3 mm) were inoculated on to wounded strawberries, and the inoculated strawberries were then fumigated with Etf at similar dose and exposure time treatments. Each test was conducted in four replicates. Fumigation with Etf at 190 g m-3 significantly reduced the growth of C. gloeosporioides on agar, but did not reduce the colonization of the pathogen on strawberries. Ethyl formate did not affect visual quality of strawberries, but damaged the calyx at 190 g m-3. Other fungi, namely Colletotrichum sp. and Botrytis sp., were found on fumigated and nonfumigated strawberries.  Key words: Colletotrichum gloeosporioides, ethyl formate, strawberries